Utilization of carbon catabolite repression for efficiently biotransformation of anthraquinone O-glucuronides by Streptomyces coeruleorubidus DM - Tao, Chen; Wang, Quyi; Ji, Junyang; Zhou, Ziyue; Yue, Bingjie; Zhang, Ran; Jiang, Shu; Yuan, Tianjie (Frontiers in Microbiology, 2024)
Carbon catabolite repression (CCR) is a highly conserved mechanism that regulates carbon source utilization in Streptomyces. CCR has a negative impact on secondary metabolite fermentation, both in industrial and research settings. In this study, CCR was observed in the Daunorubicin (DNR)-producing strain Streptomyces coeruleorubidus DM, which was cultivated in high concentration of carbohydrates. Unexpectedly, DM exhibited a high ability for anthraquinone glucuronidation biotransformation under CCR conditions with a maximum bioconversion rate of 95% achieved at pH 6, 30℃ for 24 hours. The co-utilization of glucose and sucrose resulted in the highest biotransformation rate compared to other carbon source combinations. Three novel anthraquinone glucuronides were obtained, with purpurin-o-glucuronide showing significantly improved water solubility, antioxidant activity, and antibacterial bioactivity. Comparative transcript analysis revealed that glucose and sucrose utilization were significantly upregulated as DM cultivated under CCR condition, which strongly enhance the biosynthetic pathway of the precursors Uridine diphosphate glucuronic acid (UDPGA). Meanwhile, the carbon metabolic flux has significantly enhanced the fatty acid biosynthesis, the exhaust of acetyl coenzyme A may lead to the complete repression of the biosynthesis of DNR, Additionally, the efflux transporter genes were simultaneously downregulated, which may contribute to the anthraquinones intracellular glucuronidation. Overall, our findings demonstrate that utilizing CCR can be a valuable strategy for enhancing the biotransformation efficiency of anthraquinone O-glucuronides by DM. This approach has the potential to improve the bioavailability and therapeutic potential of these compounds, opening up new possibilities for their pharmaceutical applications.